Moodle platform for the development of reading comprehension in students with learning difficulties - Robalino Cardenas, Myriam Fernanda; Sánchez Manosalvas, Olga Teresa (SATHIRI, 2025)
The improvement of the reading process and acquisition continue to be a priority, therefore the study presented evaluated the effectiveness of the implementation of a virtual classroom on the Moodle platform as support for the acquisition of reading comprehension in children with learning difficulties, for which a virtual environment based on the DUA methodology (universal learning design) and didactic strategies with gamification was proposed , applicable for children in the stage of concrete operations who attend the La Rayuela Psychopedagogical Center, in Quito. The research responded to the case study, with a mixed, descriptive, quasi-experimental approach, using a control group made up of 8 students. The WISC V intelligence scale and ACL reading comprehension tests were applied before and after the intervention with a duration of 8 weeks, obtaining quantitative statistical data, along with observations and qualitative anecdotal records. The results regarding the progress of reading comprehension learning applied to the control group were significant, demonstrating the need to integrate digital platforms, and gamification in psychopedagogical intervention techniques to improve psychoeducational processes, especially in students with specific learning difficulties.  The importance of innovation was emphasized in terms of resources and supports that can be implemented for intervention by trained personnel such as educational psychologists and/or educational psychologists for their appropriate and responsible use.
Keywords: Reading comprehension; learning difficulties; virtual classroom; gamification